KADAR SERAT KASAR DAN LEMAK KASAR SORGHUM GREEN FODDER YANG TUMBUH PADA MEDIA TANAM DAN UMUR PANEN YANG BERBEDA - Khairunnisa, Bunga Ayu Athaya; Hidayat, Nur; Hendarto, Eko; Harwanto, Harwanto (ANGON: Journal of Animal Science and Technology, 2021)
Background. This research aimed to determine the levels of crude fiber and extract ether of sorghum green fodderthat grown in growing medium and different harvesting ages. Materials and Methods. Harvest ages used namely 5, 10, and 15 days, while medium used namely fermented of urine 25%/liter and nutrition AB Mix. The research materials consisted of 2 kg sorghum seeds (Sorghum bicolor (L.) Moench), 1 liter fermented of urine, and AB Mix nutrition. The tools used are plastic 24 boxes, 2 plastic sprays and a set of tools for analysis crude fiber and extract eter based on AOAC 2002. This research used a completely randomized design (CRD) consisting of 6 treatments and 4 replications. Results. The research showed that different harvest ages had a significant effect (P<0.05) on the crude fiber and extract eter content of sorghum green fodder (SGF). Conclusion. Based on the research can be concluded that the older the harvest ages SGF, content of crude fider and extract eter more increasing. The optimal harvesting age for SGF is 15 days with urine fermented as planting medium.